Congestion-Aware Incentive Scheme Based on Double Auction for DTN - Qingfeng Jiang; Chaoguang Men; Meijuan Jia; Xiaoxu Cheng (Dianxin kexue)
To stimulate the DTN selfish nodes to cooperatively forward messages when the buffer was limited, a congestion-aware incentive scheme based on double auction for DTN was proposed. In the scheme, nodes determined the self congestion degree according to the current free buffer and message receiving rate. Combining the message delivery probability and congestion degree, nodes traded the message based on double auction model, thereby achieved the cooperation between nodes. Extensive simulations were carried out on real-world traces to evaluate the proposed scheme. The experimental results show that, due to the congestion aware, the incentive scheme can further stimulate selfish nodes to cooperatively forward messages, improve the message delivery ratio and reduce the message delivery delay.